DNA methylation markers for kidney function and progression of diabetic kidney disease - Li, Kelly Yichen; Tam, Claudia Ha Ting; Liu, Hongbo; Day, Samantha; Lim, Cadmon King Poo; So, Wing Yee; Huang, Chuiguo; Jiang, Guozhi; Shi, Mai; Lee, Heung Man; Lan, Hui-yao; Szeto, Cheuk-Chun; et al. (Nature communications, 2023)
Epigenetic markers are potential biomarkers for diabetes and related complications. Using a prospective cohort from the Hong Kong Diabetes Register, we perform two independent epigenome-wide association studies to identify methylation markers associated with baseline estimated glomerular filtration rate (eGFR) and subsequent decline in kidney function (eGFR slope), respectively, in 1,271 type 2 diabetes subjects. Here we show 40 (30 previously unidentified) and eight (all previously unidentified) CpG sites individually reach epigenome-wide significance for baseline eGFR and eGFR slope, respectively. We also develop a multisite analysis method, which selects 64 and 37 CpG sites for baseline eGFR and eGFR slope, respectively. These models are validated in an independent cohort of Native Americans with type 2 diabetes. Our identified CpG sites are near genes enriched for functional roles in kidney diseases, and some show association with renal damage. This study highlights the potential of methylation markers in risk stratification of kidney disease among type 2 diabetes individuals. Epigenetic markers are potential biomarkers for diabetes and related complications. Here, the authors identify CpG sites associated with kidney function and its subsequent decline using both single-site and multisite analyses, which are shown to have functional significance in the kidney.